2008
DOI: 10.3171/foc.2008.25.12.e4
|View full text |Cite
|
Sign up to set email alerts
|

The work horse of skull base surgery: orbitozygomatic approach. Technique, modifications, and applications

Abstract: Object The aim of this study was to describe the microsurgical anatomy of the orbitozygomatic craniotomy and its modifications, and detail the stepwise dissection of the temporalis fascia and muscle and explain the craniotomy techniques involved in these approaches. Methods Nine cadaveric embalmed heads injected with colored silicone were used to demonstrate a stepwise dissection of the 3 variations of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 85 publications
(45 citation statements)
references
References 40 publications
0
43
0
2
Order By: Relevance
“…The advantages of adding an orbitozygomatic or orbital osteotomy alone to the traditional FT craniotomy have been previously elucidated by various cadaveric studies and 3D quantitative models. 3,7,26,35,45,50 FTOZ has been shown to increase the surgical freedom and the projection angle while decreasing the amount of brain retraction required for adequate exposure. 3 However, in recent years, our experience in treating small to midsized sphenocavernous meningiomas and sphenoclinoidocavernous meningiomas has suggested that adequate exposure and maximal resection was possible with an FT craniotomy alone, followed by a combined extradural-intradural approach (Figs.…”
Section: Surgical Approachesmentioning
confidence: 99%
“…The advantages of adding an orbitozygomatic or orbital osteotomy alone to the traditional FT craniotomy have been previously elucidated by various cadaveric studies and 3D quantitative models. 3,7,26,35,45,50 FTOZ has been shown to increase the surgical freedom and the projection angle while decreasing the amount of brain retraction required for adequate exposure. 3 However, in recent years, our experience in treating small to midsized sphenocavernous meningiomas and sphenoclinoidocavernous meningiomas has suggested that adequate exposure and maximal resection was possible with an FT craniotomy alone, followed by a combined extradural-intradural approach (Figs.…”
Section: Surgical Approachesmentioning
confidence: 99%
“…A detailed description of subfascial dissection to expose the zygoma, which is commonly used in the orbitozygomatic approach, is given in previous publications. 24,31 Blunt dissection is used to free the periorbita from the superior, medial, and lateral aspects of the orbital rims. The supraorbital nerves can be freed from the supraorbital notch with blunt dissection.…”
Section: Level I Craniofacial Approach and Illustrative Casesmentioning
confidence: 99%
“…The subfascial dissection is used to elevate the temporalis fascia and muscle to preserve facial nerve branches. As we describe elsewhere, the superolateral orbital rim is removed and the sphenoid ridge flattened to facilitate full exposure of the supraclinoid ICA; this is particularly helpful in cases of BBAs [6]. The distal Sylvian fissure is dissected widely to reduce the use of retractors.…”
Section: Openingmentioning
confidence: 98%